Evaluation of matrix metalloproteases as early biomarkers for bone regeneration during the applied Masquelet therapy for non-unions. Issue 10 (October 2018) - Haubruck, P.; Heller, R.; Apitz, P.; Kammerer, A.; Alamouti, A.; Daniel, V.; Schmidmaier, G.; Moghaddam, A.
Abstract: Introduction: In the current study, we sought to determine if serum concentrations of MMPs correlate with bone regeneration occurring during the course of the Masquelet-therapy and to identify if MMPs may serve as early biomarkers reflecting successful bone regeneration and tissue remodeling. Material and methods: This study was designed as a prospective clinical observer study. We compared serum samples over the time of treatment, as a matched-pair analysis, from 10 patients who were treated successfully with the Masquelet-therapy (Responder) with 10 patients who did not respond to the Masquelet-therapy (Non-Responder). The quantitative measurement was performed with Luminex Performance Human High Sensitivity Assays according to manufacturer's instructions. The lab technician performing the Luminex assays was blinded to both patient data and clinical outcome. Results: Analysis of the expression pattern of MMP-2, -8 and -9 showed significant differences between groups. Two days after the first step of the Masquelet therapy Responder showed peak values of MMP-8 and MMP-9 that where significantly higher (p = 0.003 and p = 0.042, respectively) than in Non-Responder. In contrast serum levels of MMP-2 were lower after the first step of the Masquelet therapy in the Non-Responder group. The ratio of MMP-9 and MMP-2 was significantly higher in the Responder group two days after step I (p = 0.031) as well as 4 weeks after step II (p = 0.030). Conclusion: The findings of the current study emphasize the potential role of MMPs as biomarkers in bone remodeling. In particular, a distinct expression of MMP-2 correlates with successful bone regeneration, whereas initial overexpression of MMP-2 serum levels might identify patients that have a higher risk for a poor outcome of the Masquelet-therapy. Furthermore, we were able to introduce the serum analysis of the ratio of MMP-9 and MMP-2 as promising novel modality for early prediction of the outcome of the Masquelet therapy. Further analysis of this ratio over time subsequent to the second step might serve as an early indicator of a favorable response to the induced membrane technique.